The study of the process of alkaline precipitation purification of solutions from silicon macroscales in the ammonium-fluoride processing of beryllium-containing materials; MATEC Web of Conferences; Vol. 85 : Chemistry and Chemical Technology in XXI Century (CCT 2016) - Dyachenko A. N. Alexander Nikolaevich; Kraydenko R. I. Roman Ivanovich; Lesnikova M. Margarita; Malyutin L. N. Lev Nikolaevich; Petlin I. V. Ilya Vladimirovich (2016, 2016)
Title screen